Efficacy of educational strategies in patient involvement for safety in care: a systematic review - Raíssa Bianca Luiz; Layara Oliveira Estevam; Maria Beatriz Guimarães Raponi; Márcia Marques dos Santos Felix; Maria Helena Barbosa (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To evaluate the effectiveness of educational strategies in the involvement of hospitalized adult patient for safety in care. Method Systematic review carried out by searching for experimental and quasi-experimental studies, published from January/2010 to December/2021, in PubMed®, Cochrane Library CENTRAL, Scopus, Web of Science, LILACS, CINAHL and EMBASE. Results Twelve studies were included to involve the patient in safe care practices, five (41.7%) experimental and seven (58.3%) quasi-experimental. Different educational strategies were adopted in the articles included: verbal guidance, books, leaflets and folders (n=4; 33.3%); videos, e-books and electronic applications (n=5; 41.7%); poster, leaflets and video (n=3; 25%). Four experimental studies had a high risk of bias (80%) and all quasi-experimental studies had a low risk of bias (100%). Conclusion The use of educational strategies proved to be effective in involving the patient in safe care practices. Considering the heterogeneity between studies, it is recommended carrying out future research.